The Tomlinson Report and the third wave of Dutch Reformed mission: context and content - Saayman, W (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The author describes and analyses the congruencies and correlations between DRC mission history and Afrikaner history. He focuses in this paper on the reciprocal effects of the findings and recommendations of the Tomlinson Commission who researched the socio-economic development of Bantu Reserves within white South Africa. The Tomlinson Report had a significant influence on DRC mission in the so-called Bantu homelands within South Africa. There were specific congruencies in the area of researching and finding solutions to the “native problem” in both church and state. The preferred approach for both was to be found in the adoption of an approach based on racial separation, with language and culture as the main indicators of difference. Nevertheless the relationship cannot simply be described as collusive.